Romanticism on Ice: Coleridge, Hogg and the Eighteenth-Century Missions to Greenland - Moss, Sarah (Romanticism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractThis article discusses the influence of mid-eighteenth century Arctic missionary narratives on Samuel Taylor Coleridge and James Hogg. I suggest that these narratives offer a new context for the literary Arctic and undermine established readings of polar landscapes as the ultimate example of Romantic sublimity.